Odpowiedzi

Najlepsza Odpowiedź!
2010-04-08T23:34:22+02:00
1.
a) p=a*h /:a
h = p/a

b) p=1/2(a+b)*h /: 1/2(a+b)
h = p : (0,5a+0,5b)


2.
A)4(X-1)+2=2X+5
4x-4+2 = 2x+5 /-2x +2
2x = 7 /:2
x = 3,5

b)4X-(x-2)=3x-2
4x-x+2 = 3x-2
3x+2 =3x-2
brak rozwiązań

c)1/4+x=5-2x /+2x -1/4
3x = 4 i 3/4 /:3
x = 19/4 * 1/3
x = 19/12


2 4 2
2010-04-08T23:35:20+02:00
1. Wyznacz "h"
a) p=a*h
ah = p /: a
h = p/a

b) p=1/2(a+b)*h
1/2(a + b) h = p /: 1/2(a + b)
h = p : 1/2(a + b)

2.
A)4(X-1)+2=2X+5
4x - 4 + 2 = 2x + 5
4x - 2x = 5 + 4 - 2
2x = 7 /: 2
x = 7/2
x = 3 i 1/2

b)4X-(x=2)=3x-2
4x - x - 2 = 3x - 2
4x - x - 3x = -2 + 2
0 = 0

c)1/4+x=5-2x
x + 2x = 5 - 1/4
3x = 20/4 - 1/4
3x = 19/4 /: 3
x = 19/4 x 1/3
x = 19/12
x = 1 i 7/12
2 3 2